2017
DOI: 10.1017/s0022149x17000293
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of murine intestinal immunity by Moringa oleifera extract in experimental hymenolepiasis nana

Abstract: The potential therapeutic value of Moringa oleifera extract (MOE), due to its anti-inflammatory and anti-oxidant effects, has been reported previously. In this study, Hymenolepis nana antigen (HNA) in combination with MOE was used in immunization against H. nana infection. Adult worm and egg counts were taken, while histological changes in the intestine were observed. Mucosal mast (MMCs) and goblet cells (GCs) were stained with specific stains, while serum and intestinal IgA were assayed using enzyme-linked im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 66 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Thereafter, collection of the eggs was executed from infected rats that were euthanized on day 16th post infection. Infectious shell-free eggs were produced from the gravid segments of adult worms via agitating the egg suspension with 3 mm-diameter glass beads shortly prior to use [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, collection of the eggs was executed from infected rats that were euthanized on day 16th post infection. Infectious shell-free eggs were produced from the gravid segments of adult worms via agitating the egg suspension with 3 mm-diameter glass beads shortly prior to use [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“… 37 Finally, preclinical studies have reported a role for moringa in reducing oxidative stress and improving immune function. 38 We hypothesise that children receiving the IYCF-plus intervention will have a more mature microbiota, reduced EED, less systemic inflammation and an associated improvement in antipathogen immune cell function compared with the IYCF intervention.…”
Section: Rationale For Interventionsmentioning
confidence: 99%